Determination of deformations in soft soils with a coupled analysis-Alibey Dam - Özaydin, K; Kilic, H; Berilgen, MM; Özcoban, MS; Yildirim, S (A A BALKEMA PUBLISHERS, 2001)
In this paper, the results of a coupled analysis using the finite element method, which has been performed to investigate the stress-strain-consolidation behaviour of a dam foundation, are presented. The stress increases in the foundation soil layers due to loading of the embankments during the staged construction and the corresponding pore pressure increases and displacements have been computed. The stress increases and the immediate deformations were calculated using an elasto-plastic analysis taking into account the consolidation behaviour. In the numerical analyses, a computer code named PLAXIS was used and the calculated time-dependent settlements, lateral displacements and the pore pressures compared well with the measured values.
Keywords: Engineering